A STUDY OF POLITENESS STRATEGIES USED BY THE CHARACTERS OF THE UGLY TRUTH MOVIE - ARYANTO, WINDHI JATU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Politeness strategies, The Ugly Truth. In doing communication, people share information, tell their emotions, ask something, and so on. In order to make a good communication, people should use the words that intended to convey politeness, respect, humility, and lesser social status so that it will be easy to building a relationship with each other. Politeness is the expression of the speaker ’s intention to mitigate face threat carried by certain face threatening acts towards another. In this research, The Ugly Truth movie is chosen as the object. It is done to answer the problems of the research, they are: (1) What types of politeness strategies are used by the characters in The Ugly Truth movie? and (2) What are the factors influencing the choice of strategies used by the characters in The Ugly Truth movie?The method that is used in this research is qualitative and content or document analysis as the type of study. The data of this research are the selected utterances by the characters in The Ugly Truth movie. There are 12 dialogues used by 5 characters in the movie that analyzed as the object.The result of this research shows that there are 12 utterances using politeness strategies, consist of Bald on Record Strategy, Positive Politeness Strategy, Negative Politeness Strategy, and Off Record Strategy. Each strategy consists of three examples. The factor that influenced the different politeness strategy consists of three factors, social distance, relative power, and absolute ranking. The data showed that the social distance is the most used as the factor that influenced the different politeness strategy.The writer suggests that the next researchers use other theories in Pragmatic. The next researcher can also conduct a research on the politeness strategies in its semantic feature, or elaborate it with another field of study such as the critical discourse analysis to make this study more complete.